RNA binding proteins regulate anabolic and catabolic gene expression in chondrocytes. Issue 7 (July 2016) - McDermott, B.T.; Ellis, S.; Bou-Gharios, G.; Clegg, P.D.; Tew, S.R.
Summary: Objective: Regulation of anabolic and catabolic factors is considered essential in maintaining the homoeostasis of healthy articular cartilage. In this study we investigated the influence of RNA binding proteins (RNABPs) in this process. Design: Using small interfering RNA (siRNA), RNABP expression was knocked down in SW1353 chondrosarcoma cells and human articular chondrocytes. Gene expression and messenger RNA (mRNA) decay of anabolic (SOX9, Aggrecan) and catabolic (matrix metalloproteinase (MMP)13) factors were analysed using reverse transcription quantitative polymerase chain reaction (RT-qPCR). RNA-electromobility shift assays (EMSAs) were used to investigate RNABP interactions with the SOX9 mRNA 3′ untranslated region (UTR). Immunohistochemical localisation of MMP13 and the RNABP human antigen R (HuR) was performed in E13.5 and E16.5 mouse embryo sections. Results: SOX9 mRNA, mRNA half-life and protein expression were increased with siRNA targeting the RNABP tristetraprolin (TTP) in both HACs and SW1353s. TTP knockdown also stimulated aggrecan mRNA expression but did not affect its stability. RNA-EMSAs demonstrated that adenine uracil (AU)-rich elements in the SOX9 mRNA 3′UTR interacted with chondrocyte proteins with three specific elements interacting with TTP. HuR knockdown significantly increased MMP13 expression and also regulated the expression of a number of known transcriptional repressors of MMP13. HuR was ubiquitously expressed within mouse embryos yet displayed regional down-regulation within developing skeletal structures. Conclusion: This study demonstrates for the first time how RNABPs are able to affect the balance of anabolic and catabolic gene expression in human chondrocytes. The post-transcriptional mechanisms controlled by RNABPs present novel avenues of regulation and potential points of intervention for controlling the expression of SOX9 and MMP13 in chondrocytes.